2021
DOI: 10.1002/der2.61
|View full text |Cite
|
Sign up to set email alerts
|

Fractional CO2 laser‐assisted scar regeneration and repair: A review

Abstract: Hypertrophic scars are one of the more difficult problems to treat in our clinical practice. In this review, we cover our approach, from basic science research in our laboratory to the clinical theater on how we approach and treat these patients to improve cosmetic appearance and functional capabilities for patients suffering from hypertrophic scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In another study, the PDL and fractional CO 2 lasers were equally effective in the treatment of hypertrophic scars 11 . In the experimental study, the authors found that VEGF expression in the composited laser group was weaker than that in the PDL group and fractional CO 2 group at 7 days, 14 days, and 28 days after treatment, with significant differences between the groups 37,39 . Fractional CO 2 laser can increase the apoptosis of fibroblasts, promote collagen degradation, and reduce the secretion of VEGF by epidermal cells, so as to inhibit the proliferation of microvessels and promote the maturation and vascular regression of hypertrophic scar 40–42 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In another study, the PDL and fractional CO 2 lasers were equally effective in the treatment of hypertrophic scars 11 . In the experimental study, the authors found that VEGF expression in the composited laser group was weaker than that in the PDL group and fractional CO 2 group at 7 days, 14 days, and 28 days after treatment, with significant differences between the groups 37,39 . Fractional CO 2 laser can increase the apoptosis of fibroblasts, promote collagen degradation, and reduce the secretion of VEGF by epidermal cells, so as to inhibit the proliferation of microvessels and promote the maturation and vascular regression of hypertrophic scar 40–42 .…”
Section: Discussionmentioning
confidence: 98%
“…11 In the experimental study, the authors found that VEGF expression in the composited laser group was weaker than that in the PDL group and fractional CO 2 group at 7 days, 14 days, and 28 days after treatment, with significant differences between the groups. 37,39 Fractional CO 2 laser can increase the apoptosis of fibroblasts, promote collagen degradation, and reduce the secretion of VEGF by epidermal cells, so as to inhibit the proliferation of microvessels and promote the maturation and vascular regression of hypertrophic scar. [40][41][42] In our previous studies, we also demonstrated that PDL combined with fractional CO 2 laser could effectively treat fresh red hypertrophic scars in adults with no severe side effects.…”
Section: Posasmentioning
confidence: 99%
“…Ablative lasers used clinically for resurfacing and matrix remodeling [25,26] have been used in other in vitro engineered skin models. A fractional erbium:YAG laser was used by Schmitt et al to study the molecular effects of ablative laser treatment in a cultured skin equivalent [27].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive scarring is divided into hypertrophic or keloid scarring. They both tend to be raised above skin level with keloids representing a fibroproliferative condition extending into normal adjacent skin and continuing to be elevated while hypertrophic scars are commonly limited to wound areas and can regress by time 3 …”
Section: Introductionmentioning
confidence: 99%